Benchmark calculations of proton affinity and gas-phase basicity using multilevel (G4 and G3B3), B3LYP and MP2 computational methods of para-substituted benzaldehyde compounds - Safi, Zaki S (Journal of computational chemistry, 2021)
© 2021 Wiley Periodicals LLC.